Choice behavior after burglary victimization: moving, safety precautions, and passivity - Wollinger, Gina Rosa (European journal of criminology, 2017)
Several studies on burglary concern the psychological impact on victims of burglary. However, little research exists on changes in behavior with regard to burglary experiences. The present analysis focuses on choice behavior after a burglary by differentiating moving and safety precaution behavior as well as passivity. Here, a sample of N = 1329 victims of burglary from five big cities in Germany is used. The main findings indicate that psychological strain, age, housing condition, household income, social cohesion, and social disorganization are relevant predictors of choice behavior after a burglary. As such, different cost and benefit aspects will be considered as explanations for behavioral reactions.